Modelling and Energy Analysis of Solar Charging Facility for Electric Vehicles in Chile - Scarlett Allende (Renewable Energy and Sustainable Development, 2019)
This paper presents simulation and energy evaluation of a photovoltaic charging centre intended to supply the demand of 244,000 electric vehicles in Chile. According to the obtained results, the transportation system was feasible from the solar radiation, energy consumption, geographic zone, type of PV farm and other sources. Notably, the studied region has a solar potential to supply 10% of the total domestic cars existing in Santiago, providing a total energy of 253.723 GWh/yr. Furthermore, based on the study factors, the design of the system consists of approximately 428,590 PV modules and an average power generation of 31.89 W/hour for one single module. Finally, the configuration of a solar charging facility allows applying a new method of energy supply to electric cars that improves the environmental conditions of the city and encourages sustainable development in the transport sector.